ANALISIS SOSIOLOGI OLAHRAGA TERHADAP PARTISIPASI MASYARAKAT DALAM AKTIVITAS OLAHRAGA - Siregar, Yan Indra; Arima, Putra; Hasibuan, Marto; willi, Dian Asifa; Sillahi, Putri Anjely; Depipesei, Amos; Abadi, Yunus (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze community participation in sports activities through the perspective of sports sociology. The research method used is a literature study with a qualitative descriptive approach. Research data were obtained from various national journals published within the last 10 years discussing community participation in sports, sports motivation, sports facilities, and social relations in sports activities. The results of the study show that community participation in sports is influenced by various social factors, such as environment, motivation, healthy lifestyle awareness, social support, and the availability of sports facilities and infrastructure. Besides functioning to maintain physical health, sports also play an important role in building social interaction, community solidarity, and healthy lifestyles. Government support through the provision of public sports facilities and community sports programs also has a positive influence on increasing community participation in sports. Therefore, cooperation between the government, social environment, and society is needed to create a sustainable sports culture and improve the quality of community life.